ANALISIS MODEL PEMBELAJARAN KOOPERATIF: IMPLIKASI TERHADAP HASIL BELAJAR SISWA DI KELAS SEKOLAH DASAR - Salma Kusuma Listiani; Farah Abidah Maryam; Alfaina Mafazah Musallamah; Nurlaila Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is a literature review that examines cooperative learning models and their influence on learning outcomes and student engagement at the elementary school level. Based on a review of various literature concerning the principles, characteristics, and types of cooperative learning such as STAD, TGT, Jigsaw II, and NHT, along with relevant empirical evidence, it was found that cooperative learning can improve students’ cognitive, affective, and psychomotor abilities while also strengthening their behavioral, emotional, and cognitive engagement. The success of its implementation is influenced by task designs that are able to build positive interdependence and individual responsibility, teachers’ ability to manage groups, the support of facilities and infrastructure, as well as the application of process evaluation to avoid the emergence of the free-rider phenomenon. Several obstacles frequently encountered include the dominance of teacher-centered methods, limited instructional time, differences in students’ abilities, and the inadequate readiness of teachers and supporting facilities. Therefore, this study recommends teacher training related to cooperative learning techniques, the utilization of collaborative technology to monitor the contribution of each group member, the use of clear group process assessment rubrics, as well as further research in the form of quasi-experimental or mixed-method studies to measure the effect of cooperative learning on student engagement and learning outcomes within the context of elementary schools in Indonesia. The findings of the study indicate that cooperative learning, when implemented and managed properly, can become an effective strategic alternative for improving the quality of learning and student participation in elementary schools.